2021
DOI: 10.3390/microorganisms9020363
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation of the Leishmania infantum HSP70-II Null Mutant Induces Long-Term Protection against L. amazonensis Infection in BALB/c Mice

Abstract: Leishmania amazonensis parasites are etiological agents of cutaneous leishmaniasis in the New World. BALB/c mice are highly susceptible to L. amazonensis challenge due to their inability to mount parasite-dependent IFN-γ-mediated responses. Here, we analyzed the capacity of a single administration of the LiΔHSP70-II genetically-modified attenuated L. infantum line in preventing cutaneous leishmaniasis in mice challenged with L. amazonensis virulent parasites. In previous studies, this live attenuated vaccine h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 54 publications
(98 reference statements)
0
10
0
Order By: Relevance
“…BALB/c VL mice model, vaccinated subcutaneously with 10 7 Li∆HSP70-II stationary promastigotes in the right footpad, showed a reduction in liver damage and rapid parasite-specific IFN-γ production by CD4 + and CD8 + T cells; however, this vaccine failed to control the chronic phase of the disease [251]. Li∆HSP70-II vaccinated BALB/c mice controlled the progression of CL caused by L. amazonensis infection, with enhanced IFN-γ and systemic Th2 mediated humoral response, and reduction of IL-10 secretion that favours the IFN-γ to activate leishmanicidal activity by macrophages [252].…”
Section: Live Attenuated Vaccinementioning
confidence: 99%
“…BALB/c VL mice model, vaccinated subcutaneously with 10 7 Li∆HSP70-II stationary promastigotes in the right footpad, showed a reduction in liver damage and rapid parasite-specific IFN-γ production by CD4 + and CD8 + T cells; however, this vaccine failed to control the chronic phase of the disease [251]. Li∆HSP70-II vaccinated BALB/c mice controlled the progression of CL caused by L. amazonensis infection, with enhanced IFN-γ and systemic Th2 mediated humoral response, and reduction of IL-10 secretion that favours the IFN-γ to activate leishmanicidal activity by macrophages [252].…”
Section: Live Attenuated Vaccinementioning
confidence: 99%
“…Finally, subcutaneous vaccination with the LiΔhsp70-II line prevents disease being caused by L. major [74] in murine self-healing CL and a CL progressing to VL models. It also protects against L. infantum [86] and L. amazonensis [87]. In sum, the idea that a single vaccine…”
Section: Trends In Parasitologymentioning
confidence: 99%
“…It is also relevant to know whether the multiplication dynamics of the vaccine parasite are influenced by infection with virulent Leishmania parasites. In this regard, assays performed with the LiΔhsp70-II vaccine have shown that the persistence and replicative capacity of these attenuated parasites are not altered by a subsequent infection with virulent forms of either L. major, L. infantum, or L. amazonensis [74,86,87]. Another safety issue is whether attenuated parasites can multiply and complete their cycle in the vector.…”
Section: Trends In Parasitologymentioning
confidence: 99%
“…Whole-killed parasites (Coutinho De Oliveira et al 2020, Nagill andKaur 2011). fractionated leishmania antigen (Giraud et al 2019;Coutinho et al 2020) recombinant proteins (made by genetically engineered cells) (Kumar and Samant 2016;Duthie et al 2018;Hobernik and Bros 2018) and liveattenuated pathogens (Karmakar et al 2021;Soto et al 2021) are among the vaccines that have been synthesized and are under clinical trials. Third-generation vaccinations are being researched.…”
Section: Use Of Vaccinesmentioning
confidence: 99%